AccessNeurology Walkthrough. Issue 1 (3rd April 2022) - Bishop, Marlene M.
Abstract: McGraw-Hill AccessNeurology is an online collection of neurology resources covering the study of the central nervous system for students, instructors, researchers, residents, and clinicians. The collection includes over 40 books, as well as drug information, case studies, review questions, videos, lectures, and animations. This article will review content, layout, navigation, special features, and user experience.